Midwives’ Role in Stimulating Breastfeeding Behavior Toward Exclusive Breastfeeding at Kebun Handil Puskesmas, Jambi - Nur Fauziah Putri Auliah; Adila Solida; Rizalia Wardiah; Asparian Asparian; Herwansyah Herwansyah (International Journal of Health Engineering and Technology, 2025)
Data on exclusive breastfeeding from 20 Community Health Centers (Puskesmas) in Jambi City show that the achievement rate at Kebun Handil Health Center was 42.37% in 2021. In 2022, the rate decreased by 2.57% to 39.8%, and increased by 8.17% in 2023 to reach 47.97%. However, this figure remains far below the national target of 80%. This study aims to determine the role of midwives in stimulating behavioral changes among breastfeeding mothers in providing exclusive breastfeeding within the working area of Kebun Handil Health Center, Jambi City. This research employs a qualitative method with a descriptive design, involving 11 informants consisting of key informants (Head of the Health Center), main informants (midwives at auxiliary health posts and midwives responsible for maternal and child health), supporting informants (breastfeeding mothers), and triangulation/additional informants (midwives in charge of child health programs and breastfeeding mothers). The findings show that midwives at Kebun Handil Health Center have played an optimal role in delivering services and providing education about exclusive breastfeeding to the community. However, many mothers still do not exclusively breastfeed due to various factors, including economic conditions, socio-cultural influences, lack of knowledge, and inadequate facilities and infrastructure to support breastfeeding practices.